Know ye, that we have granted, and by these presents do grant, licence and authority to John Foster Williams mariner, commander of the [blank] ... to fit out and set forth the said [blank] in a warlike manner, and by and with the said [blank] and the crew thereof ... to attack, subdue and take all ships and other vessels whatsoever carrying soldiers, arms ... or any other contraband goods to any of the British armies or ships of war employed against these United States . - Williams, John Foster, 1743-1814 ([publisher not identified], 1777)
Form for Congressional license to attack British ships assigned to "John Foster Williams" in manuscript, but unsigned and undated.